SISTEM INFORMASI PENGGAJIAN TKS (TENAGA KERJA SUKARELA) BIDAN DAN PERAWAT PADA PUSKESMAS SUNGAI RENGAS: Visual basic, Information System, Salary - -, Mulyadi (JURNAL AKADEMIKA, 2019)
The software used is using Visual Basic 6.0 programming and the database used by MySql. The devices built are about Payroll Information System TKS (Voluntary Workers) Midwives and Nurses at the Sungai Rengas Health Center. The forms of software that will be implemented consist of interface implementation, namely login, main menu, input data display consisting of Employee data input data, Picket data input, and Salary data input, then output data display ie employee report output, picket report , salary reports and then exit the application.